2006
DOI: 10.1016/j.ultsonch.2005.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic degradation of poly(vinyl alcohol) in aqueous solution

Abstract: Solution of poly(vinyl alcohol) in water with different concentrations (by weight 1%, 1.5%, 2%) and different volumes (50, 75 and 100 ml) were subjected to ultrasonic degradation. A method of viscometry was used to study the degradation behavior and kinetic model was developed to estimate the degradation rate constant. The degradation rate constant was correlated with the power input due to ultrasonic irradiation and reaction volume. It was found that rate constant decreases as the reaction volume and concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…The most generally used methods such as acid based [5], radiation based (treatment with ionizing radiation) [6] and enzymatic methods [7] suffer from important drawbacks as higher treatment cost especially in the case of enzymatic and ionizing radiation methods and uncontrolled molecular weight reduction with some changes in chemical identity especially in the case of acid based methods [8,9]. The other methods based on ultrasound [10,11] and microwave irradiation [9,12] have good potential for efficient depolymerization. The development of cost effective and efficient methods for degradation of polymer is most important and the issues related to scale up should also be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The most generally used methods such as acid based [5], radiation based (treatment with ionizing radiation) [6] and enzymatic methods [7] suffer from important drawbacks as higher treatment cost especially in the case of enzymatic and ionizing radiation methods and uncontrolled molecular weight reduction with some changes in chemical identity especially in the case of acid based methods [8,9]. The other methods based on ultrasound [10,11] and microwave irradiation [9,12] have good potential for efficient depolymerization. The development of cost effective and efficient methods for degradation of polymer is most important and the issues related to scale up should also be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…From the experimental data, it is clear that the degradation rate decreases with increasing solution concentration, so ''n'' is negative. Harkal et al 37 was found that the order of ultrasonic degradation reaction for PVA obtained from this kinetic model is À1.…”
Section: Kinetic Modelmentioning
confidence: 88%
“…Harkal et al was found that the order of ultrasonic degradation reaction for poly (vinyl alcohol) obtained from this kinetic model is -1. 47 It is noted that solution concentration (g/L) is constant and the total molar concentration (mol/L) increases during the degradation of polymer. The solution of differential Eq.…”
Section: Kinetic Modelmentioning
confidence: 99%